Acute Iatrogenic Agranulocytosis: A Rare and Dire Case of an Adverse Drug Reaction to Be Aware - André, Diogo; Caldeira, Mónica; Gouveia, Fabiana; Nascimento, Rafael; Chaves, António; Brazão, Maria (Case Reports in Hematology, 2020)
Background. Iatrogenic agranulocytosis (IA), by nonchemotherapeutic drugs, is a rare adverse event, resulting in a neutrophil count under 0.5 × 109 cells/L with fever or other suggestive signs of infection. Methods. This paper discusses the possible mechanisms responsible for agranulocytosis induced by nonchemotherapeutic drugs. It also describes three cases as well as potential ways to handle such iatrogenic situations. Conclusion. Neutropenia under 0.1 × 109 cells/L predispose patients to potentially fatal infections. Empiric broad-spectrum antibiotic and hematopoietic growth factors may be helpful in shortening hospitalization and prevent further infectious complications. Not all drugs associated with IA require frequent hematological monitoring, except medications such as clozapine, ticlopidine, and antithyroids.